Pemikiran Pendidikan Islam Perspektif al-Ghazali - Musfioh, Imroh Atul (SYAMIL: Journal of Islamic Education, 2014)
One of Moslems who have great ideas and was known as a reformer (mujaddid), among others, is al-Gazali. Socio-cultural conditions at the time, namely the emergence of political disstability that have an impact on the fragmentation of Muslims, the destruction of religion and morality. This situation makes him becoem a hero and Islamic Defenders Argumentator (hujjah al-Islam) as his responsibility to fix the blind thoughts and actions that shake the Muslims’ life. The purpose of education is to get closer to Allah SWT and not oriented only in world interests. So that, the curriculum presented should include three terms, called jasmaniyah, 'aqliyyah and akhlaqiyyah. The opinion is based on two approaches, Fiqh and Sufism. This thought seems systematic and comprehensive, and also consistent with the attitude and personality as a Sufi and Faqih. The concept of education offered, if applied in the present seems still appropriate. Beside,  the needs should be perfected in accordancing with local knowledge where the education implemented.